A Critical Interpretation on Artava : A Brief Review - Dhakad, Jyoti; Pandya, Ashwin; Pawar, Shivaji (International Research Journal of Ayurveda & Yoga, 2021)
According to Ayurveda, a woman’s health begins during the fetal stage, which defines the steps to produce a healthy female infant. The ancient Ayurvedic sages carefully studied the anatomical and physiological characteristics of women of different ages. Similarly, to the river. In Ayurveda, the regimens to follow during menstrual and post-menstrual cycles are well advised. Women’s disobedience to these regimens is the leading cause of gynecological and systemic diseases. Aside from the systemic diseases. Artavavaha Srotas (female reproductive system) is extensively defined in Ayurveda in terms of Moolsthana (source), pathophysiology, clinical conditions, and ayurvedic management. Artavavaha Srotas (female reproductive system) resembles the female reproductive system as it is described in modern medicine. One of the most common causes of poor obstetric history may be anatomical defects of the reproductive system. It tends to be a definition of the diameter of the entire vulva rather than the vaginal introitus. This explains why women are immune to a wide variety of diseases. In Ayurveda, the regimens to follow during menstrual and post-menstrual cycles are well advised. The most common cause is disobedience to these laws. In Ayurveda, the word Bhaga refers to the Smaramandira and Yoni, which are similar to Vulva. It has a length of 12 angul. (9 inches). It tends to be a definition of the diameter of the entire vulva rather than the vaginal introitus. This explains why women are immune to a wide variety of diseases. In Ayurveda, the regimens to follow during menstrual and post-menstrual cycles are well advised.